A Prototype of a Robot Capable of Tracking Anyone with a High Body Temperature in Crowded Areas - Chaari, Mohamed Zied; Aljaberi, Abdulaziz (International Journal of Online and Biomedical Engineering (iJOE), 2021)
People's health and the world economy around worldwide are under the impact of the virus. Controlling the propagation of coronavirus is extraordinarily challenging after the seventeen months since the pandemic outbreak. This research will represent the efficiency of robots in helping humanity in facing the Corona pandemic and the global health crisis. According to the quick and widespread Covid-19 contagion globally, healthcare service demand increased staff with less availability. In this crisis, robotics is the safe solution at a low price to support people to fight Covid-19. Furthermore, it is essential to relax lockdown restrictions after the increase in the number of people vaccinated. In this context, we designed a mobile robot with a thermal temperature scanner for pedestrians and identified those with abnormal temperatures over 39°C in public places and track them in real time. This robot features a long-lasting, lightweight battery and a high-quality thermal camera. Our primary target is to reduce the risk of transmission between people. We use a single-board computer and a thermal camera to detect unusual fevers near real-time to achieve this design and prototyping. In addition, we use image processing to detect target pedestrians and a control system to guide the robot. This robot can bypass any potential obstacles that can prevent it from moving around and cause problems. The development of this robot mainly focuses on the real-time measurement of body temperature at a distance of two meters. The compensation algorithm can coordinate between the mechanical parts of the robot and high-efficiency design.